2013
DOI: 10.1155/2013/215305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cholesterol Removal Processing Usingβ-Cyclodextrin on Main Components of Milk

Abstract: Various concentrations (0%, 0.5%, 1% and 1.5%) of β-CD were mixed with different fat contents (1%, 2.5% and 3%) of raw (unhomogenized) and homogenized milk at two mixing temperatures of 8 and 20°C. The cholesterol residue, fat, protein, lactose, solid nonfat (SNF), density, and ash content of milk were measured for each treatment. The results statistically analysed and showed that the cholesterol content of milk remarkably decreased as the β-CD was increased particularly in homogenized milk at 20°C. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 23 publications
4
8
0
Order By: Relevance
“…A recent study by Alonso et al has demonstrated that the addition of β-CD and Lactobacillus acidophilus cultures to diet can reduce the levels of total cholesterol and LDL-cholesterol in the blood serum of pigs [ 5 ]. The application of CDs in food products and processing is also increasing, and β-CD has been shown to be effective in removing cholesterol from milk [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Alonso et al has demonstrated that the addition of β-CD and Lactobacillus acidophilus cultures to diet can reduce the levels of total cholesterol and LDL-cholesterol in the blood serum of pigs [ 5 ]. The application of CDs in food products and processing is also increasing, and β-CD has been shown to be effective in removing cholesterol from milk [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maskooki et al . () reported a study of cholesterol removal by β‐CD at various concentrations (0, 0.5, 1 and 1.5%) when mixed with different fat contents (1, 2.5 and 3%) of raw (unhomogenized) and homogenized milk. Their results showed that the cholesterol content of milk was remarkably decreased, with β‐CD increased up to the level of 1% β‐CD (maximum cholesterol reduction was reached).…”
Section: Resultsmentioning
confidence: 99%
“…Maskooki et al [31] reported that, the outer surface of -CD macromolecules has affinity to absorb the negative charges that cover the protein surfaces. Subsequently, parts of protein together with -CD:cholesterol inclusion complexes leave during centrifugation and separation process.…”
Section: Protein Quantificationmentioning
confidence: 99%
“…The yellow-orange colour of yolk is due to carotenoid pigments, primarily xanthophylls with minor amount of carotene [31]. Awad et al [27] reported that β-carotene concentrations of egg yolk powder treatment with β-CD were lower than those of untreated egg yolk powder.…”
Section: Colour Determinationmentioning
confidence: 99%